ANALISIS VEGETASI MANGROVE SEKITAR TAMAN NASIONAL RAWA AOPA WATUMOHAI DESA PASSARE APUA KECAMATAN LANTARI JAYA KABUPATEN BOMBANA SULAWESI TENGGARA - Izal Izal; Analuddin Analuddin; Muhsin Muhsin (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACT The objective of this study was to elucidate the species composition, vegetation structure and ordination pattern of mengroves in the Passare Apua village at Lantari Jaya district, Bombana regency, South East Sulawesi. The transect method and sampling quadrat were used in this study. The growth parameters of mangroves were measured at 30 plots (100 m2 wide each). The number of individual mangroves on the basis of growth stages including trees, poles, saplings and seedlings were counted, while the environmental condition such as temperature, salinity, pH and organic matter content were analyzed. The ecological indicators such as density, frequency, dominance, importance value indice and ordination pattern were estimated. The results showed that there existed 7 species and 3 families of mangroves at the study site. The Rhizophora apiculata Blume was the highest importance value indice (125-150%), indicated as the most dominant mangrove that supports mangroves ecosystem stability in this area. The ordination pattern of mangrove vegetation across the study area formed 3 groups, Group A comprised by stands I, III and IX; Group B consists of stands II, V, VI, VII and VIII, while group C composed by stands IV and X.Keywords : Mangrove composition, Mangrove Structure, Importance Value,                     Ordination Pattern